Stuttering and bilingualism - Byrd, Courtney (Henry Stewart Talks, 2019)
Monolingual and bilingual speakers, Review of stuttering literature, Bilingualism a risk factor for stuttering, The potential of false positive identification, Risk factors involved in a false positive identification of stuttering, Typical speech disfluencies that can overlap with stuttering, Clinical evaluation of frequencies and types of disfluencies, Improving the diagnostic markers of stuttering